Monitoring of freshwater toxins in European environmental waters by using novel multi‐detection methods. (2nd September 2016) - Rodriguez, Ines; Fraga, Maria; Alfonso, Amparo; Guillebault, Delphine; Medlin, Linda; Baudart, Julia; Jacob, Pauline; Helmi, Karim; Meyer, Thomas; Breitenbach, Ulrich; Holden, Nicholas M.; Boots, Bas; et al.
Abstract: Monitoring the quality of freshwater is an important issue for public health. In the context of the European project μAqua, 150 samples were collected from several waters in France, Germany, Ireland, Italy, and Turkey for 2 yr. These samples were analyzed using 2 multitoxin detection methods previously developed: a microsphere‐based method coupled to flow‐cytometry, and an ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) method. The presence of microcystins, nodularin, domoic acid, cylindrospermopsin, and several analogues of anatoxin‐a (ATX‐a) was monitored. No traces of cylindrospermopsin or domoic acid were found in any of the environmental samples. Microcystin‐LR and microcystin‐RR were detected in 2 samples from Turkey and Germany. In the case of ATX‐a derivatives, 75% of samples contained mainly H2 ‐ATX‐a and small amounts of H2 ‐homoanatoxin‐a, whereas ATX‐a and homoanatoxin‐a were found in only 1 sample. These results confirm the presence and wide distribution of dihydro derivatives of ATX‐a toxins in European freshwaters. Environ Toxicol Chem 2017;36:645–654. © 2016 SETAC